2020
DOI: 10.25237/revchilanestv49n04-09
|View full text |Cite
|
Sign up to set email alerts
|

The prophylactic effect of intravenous magnesium infusion on postoperative sore throat after thyroid surgery. A randomized clinical trial

Abstract: The reported incidence of postoperative sore throat (POST) varies widely from 14.4 to 100% with maximum severity at 4 to 6 postoperative hour. Nonetheless, it has increasingly become a common clinical problem particularly in thyroid surgery. Although POST usually resolves spontaneously in few days, it is likely to be the most common complaint. Driven by the increased number of patients with post-intubation sore throat following thyroid surgery, the aim of the present study was to evaluate the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Many routes of administration have been used for MgSO 4 such as IV, nebulization, gargle, and lozenges. [15][16][17][18][19] The incidence of POST was less with group nebulized with magnesium, that is, Group N (29% at 0 h) compared to Group I where magnesium was administered intravenously (52.86% at 0 h). The incidence at the 1 st h (29.17% vs. 52.86%) and at the 6 th h (25% vs. 48.57%) also showed lesser POST in Group N nebulized with magnesium sulfate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many routes of administration have been used for MgSO 4 such as IV, nebulization, gargle, and lozenges. [15][16][17][18][19] The incidence of POST was less with group nebulized with magnesium, that is, Group N (29% at 0 h) compared to Group I where magnesium was administered intravenously (52.86% at 0 h). The incidence at the 1 st h (29.17% vs. 52.86%) and at the 6 th h (25% vs. 48.57%) also showed lesser POST in Group N nebulized with magnesium sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of POST in the previous studies with IV magnesium sulfate was 37.5-50% and with nebulized magnesium sulfate was 19.2-30%. 15,[19][20][21] Hence, sample size was estimated based on the previous study of Sheikh et al, 17 where the incidence of POST was 48% with IV magnesium sulfate. Assuming a reduction of 50% in incidence with nebulized magnesium sulfate with alpha error 0.05 and power 80%, we acquired sample size of 68 per group.…”
Section: Sample Size Calculation and Statistical Analysismentioning
confidence: 99%
“…The reports regarding the analgesic efficacy of magnesium sulfate have been controversial [13,[18][19][20]. Mostafa et al [15] evaluated the prophylactic effect of intravenous infusion of magnesium on postoperative sore throat after thyroid surgery. They evaluated 80 female patients in two groups of 30 mg/kg magnesium sulfate (test) and isotonic saline (control).…”
Section: Discussionmentioning
confidence: 99%
“…The reports regarding the analgesic efficacy of magnesium sulfate have also been controversial [13,14]. Mostafa et al [15] evaluated the prophylactic effect of intravenous infusion of magnesium on postoperative sore throat after thyroid surgery and reported that it significantly decreased the incidence and severity of sore throat after thyroidectomy. Hamed and Al-Saeed [16] assessed the efficacy of intravenous magnesium sulfate versus intravenous paracetamol on pain in children after tonsillectomy and the need for analgesics and reported that magnesium sulfate had superior analgesic efficacy compared with paracetamol, and decreased the need for analgesics.…”
Section: Introductionmentioning
confidence: 99%